Pembinaan Karakter Religius Siswa Melalui Kegiatan Rohani Islam (ROHIS) di SMA Negeri 1 Kecamatan Tebing Tinggi Kabupaten Serdang Bedagai - Irmayani, Dewi; Kasran; Novianti, Winda (STAI Tebing Tinggi Deli, 2024)
This research uses a qualitative descriptive approach with a field research study design. This research aims to determine the planning, implementation and evaluation related to fostering students' religious character through Spiritual Islamic activities (Islamic Spirituality) at State Senior High School 1, Tebing Tinggi District, Serdang Bedagai Regency. This research obtained information by collecting data through observation, interviews and documentation from primary and secondary data sources. Primary data comes from several informants as sources for interview activities, namely the principal, deputy principal, Islamic Spirituality teacher/counsel, Guidance Counseling teacher and representatives of several students who actively take part in Islamic Spirituality activities at State Senior High School 1 Tebing Tinggi District Serdang Bedagai Regency. Data was analyzed using data reduction techniques, data presentation, and making conclusions/verification. Research data is checked for validity using extended observations, increasing persistence, triangulation and using reference materials.The results of this research show that 1) Planning for Islamic Spiritual activities in developing the religious character of students at State Senior High School 1, Tebing Tinggi District, namely: planning related to schedules, work programs/activities, materials, methods and infrastructure that support Spiritual activities Islam. 2) Implementation of Islamic Spiritual activities in developing the religious character of students at State High School 1, Tebing Tinggi District, namely: Opening of Islamic Spiritual activities by the moderator, followed by reading the holy verses of the Koran, taking attendance of students, then the main activity in delivering the material by Islamic Spiritual Guide / murabbi. followed by discussion based on the theme/discussion material, ending with reflections and closing. Some of the processes include: The coach provides a positive example (exemplary) to students, fosters awareness of faith in students, carries out several habits which are carried out repeatedly and motivates students so that Islamic spiritual activities carried out with this process can make students have character. religious. 3) Evaluation: It can be seen based on several work programs for Islamic Spiritual activities that have been implemented, based on the attendance of Muslim students who take part in Islamic Spiritual activities, based on the students' daily attitude values ​​and the notes in the Guidance Counseling guidance book, in this case, the nature of a person's religious character It still cannot be measured, but it comes back to self-awareness and environmental factors. Religious character development is carried out as a form of effort to become a better person